2016
DOI: 10.18002/rama.v11i1.3309
|View full text |Cite
|
Sign up to set email alerts
|

Demandas técnico-táticas e fisiológicas de combates da luta olímpica

Abstract: ResumoAnálises das demandas técnico-táticas e fisiológicas dos combates da luta olímpica são importantes porque mostram informações essenciais para o desenvolvimento de treinamentos contextualizados e preparação física específica para lutadores. Por isso, o objetivo dessa revisão é mostrar características do combate de luta olímpica nos estilos livre, feminino e greco-romana. A análise de tempo-movimento apresentada nesse artigo é componente principal para inferências sobre a intensidade em relação à taxa de e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
1
6
0
1
Order By: Relevance
“…In agreement with previous investigations, our research revealed that technical wrestling skills, i.e. reverse waistlock from a standing position (D5) and trunk grip gut wrench (D4) were also indicated as important success factors [ 3 , 12 , 16 , 50 , 51 ]. This is mainly attributed to the fact that higher muscle mass and anaerobic power can help the wrestler perform technical manoeuvres more easily.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In agreement with previous investigations, our research revealed that technical wrestling skills, i.e. reverse waistlock from a standing position (D5) and trunk grip gut wrench (D4) were also indicated as important success factors [ 3 , 12 , 16 , 50 , 51 ]. This is mainly attributed to the fact that higher muscle mass and anaerobic power can help the wrestler perform technical manoeuvres more easily.…”
Section: Discussionsupporting
confidence: 91%
“…anthropometric measurements of wrestlers at various levels of competition [ 8 , 9 ], development of motor abilities [ 3 , 7 , 10 ], technical and tactical wrestling skills [ 3 , 11 , 12 ] or physical performance [ 3 , 10 , 11 , 13 ] in the novice-expert domain. These studies showed that anthropometric measurements [ 14 , 15 ], upper and lower body strength, anaerobic power, strength endurance [ 3 , 7 , 10 , 11 , 13 , 16 ], response time [ 17 ] and technical wrestling skills such as suplex throw, throw over the hip (head and arm) and rear takedown by front waistlock [ 12 , 16 , 18 ] differentiated successful and less successful wrestlers of both styles [ 12 , 16 ]. Surprisingly, a lot of researchers omitted other important components of sports preparation, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Olympic wrestling has undergone numerous changes regarding fight duration [ 1 ]. In 1896, there was no time limit.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies Chaabène et al 18 and Tabben et al 19 observed that during the Kumite, elite Karate athletes performed more often techniques based on upper limbs while the Mawashi geri chudan was the most commonly employed lower limb technique. Another variable considered in notational studies is related to the tactic employed by the athlete during combat, a skill that when linked with the technique could result in enhanced performance 20 . Two tactical behaviours in Kumite Karate, perception and anticipation, have not been thourougly investigated to date.…”
Section: Introductionmentioning
confidence: 99%